2023
DOI: 10.35848/1347-4065/accaef
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculation analysis and photovoltaic properties of Cu compound-added perovskite solar cells

Abstract: Experiments and first-principles calculations were performed to investigate the effects of Cu substitution in CH3NH3PbI3 perovskite crystals. The first-principles calculations indicated that the energy level of the Cu d orbital formed above the VB maximum would be an acceptor or defect level. The effect of Cu addition on device properties was investigated, and the device with added 2% Cu provided higher efficiencies than the standard device. On the other hand, the decrease in short-circuit current density with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…The energy gap and carrier effective mass were calculated from the band structure, and the information on orbitals was obtained from the partial density of states (pDOS). The details of the calculation method are described in the previous papers [39].…”
Section: Device Fabrication and Computational Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy gap and carrier effective mass were calculated from the band structure, and the information on orbitals was obtained from the partial density of states (pDOS). The details of the calculation method are described in the previous papers [39].…”
Section: Device Fabrication and Computational Conditionsmentioning
confidence: 99%
“…In this study, the effects of the addition of Cu compounds to the perovskite precursor solution and the substitution of Pb with Cu on the device properties and electronic structure were investigated [39]. The amount of Cu added was varied in the range of 0, 1, 2, 3, and 12.5%, and the current-voltage characterization and X-ray diffraction measurements were performed.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42][43] However, first-principles calculations and experiments have shown that the introduction of Cu 2+ into the B site in perovskite crystals destabilizes the crystal structure and reduces device stability. 44) For device durability, it was reported that the simultaneous addition of Cu 2+ and stable organic cations compensates the structural destabilization caused by Cu 2+ substitution. However, the Cu 2+ substitution affects the electronic structures, and the energy level of the Cu-d orbital formed in the forbidden band acts as a defect level, and the carrier recombination causes a decrease in short-circuit current density.…”
Section: Introductionmentioning
confidence: 99%
“…To stabilize the perovskite structures, various cations such as formamidinium (HC(NH 2 ) 2 , FA) [11,12], ethylammonium (CH 3 CH 2 NH 3 , EA) [13,14], or guanidinium (C(NH 2 ) 3 , GA) [15][16][17][18], which have larger ionic radii than MA, have been introduced at the MA site, and their stabilities were improved to a certain extent. The introduction of alkali metals such as cesium (Cs) [19][20][21], rubidium (Rb) [22][23][24], potassium (K) [25][26][27][28], and sodium (Na) [29][30][31] was also effective since these alkali elements do not desorb from the perovskite compounds.…”
Section: Introductionmentioning
confidence: 99%